STUDI POTENSI DAN KESESUAIAN LAHAN UNTUK PERENCANAAN PENGEMBANGAN TANAMAN PANGAN DAS WAIKOMO KABUPATEN LEMBATA, NUSA TENGGARA TIMUR - I Wayan Rusna (Environmental Research Center (PPLH) of Udayana University)
A Study on land potential and suitability for farming of agricultutral food crop plants wasconducted at Waikomo watershed, Lembata Regency, Nusa Tenggara Timur Province. Aimsof this study were to identify location of the land which was suitable for agriculture, and toidentify land suitability and limiting factors. This study was carried out trough field surveyby using map of slope class as land unit. Identification and soil sampling were carried out oneach land unit. Land potential for agriculture was analysed by criteria of land capability,while classification of land suitability was analysed by criteria of land suitability. Results ofthe land capability study showed that there were four land units which were suitable to beplanted agricultural crops. Theplants which could grow there were corn, sorghum, Phaseolusbeans, and sweet potatoes.